Analisis Nilai Tambah Produk Olahan Lidah Buaya Sebagai Bahan Kosmetika Alami - Putri, Levana Masitajasmin; Novitaningrum, Restie; Cahyaningtyas, Nur Indah (Journal of Agribusiness, Social and Economic, 2025)
Consumer awareness of ecofriendly products has boosted the growth of the natural cosmetics industry, including those derived from aloe vera. However, its potential remains underutilized, particularly in processing and value addition. This study analyzes the value added of two aloe vera based cosmetic products, powder face masks and peel off face masks produced by PT. Saesha Cantika Indonesia in Bogor Regency. Using the Hayami value added method and a case study approach, the results show high value added for both products: IDR 125,714/kg (78%) for the powder mask and IDR 80,000/kg (67%) for the peel off mask. The powder mask demonstrates better raw material efficiency and a higher contribution to labor income, while the peel off mask offers greater profitability with an 80% profit rate. Value added distribution for the powder mask is 34% to labor and 66% to profit, whereas for the peel off mask it is 20% to labor and 80% to profit. These findings indicate that both products possess substantial economic potential with distinct advantages. The powder mask suits labor intensive business strategies that support local economic empowerment, while the peel off mask aligns with premium market strategies emphasizing high profit margins. Overall, processing aloe vera into cosmetic products provides considerable economic benefits and opportunities for agribusiness development based on local natural resources.